Parkinson's disease: Evolution of the scientific literature from 1983 to 2017 by countries and journals. (April 2019) - Robert, C.; Wilson, C.S.; Lipton, R.B.; Arreto, C.-D.
Abstract: This study charts the evolution of the scientific literature on Parkinson's disease (PD) from 1983 to 2017 to inform communities of scientists, physicians, patients, caregivers and politicians concerned with PD. Articles published in journals indexed in the Science Citation Index-Expanded database of the Web of Science were retrieved and analyzed in seven five-year periods: 1983–1987, 1988–1992, 1993–1997, 1998–2002, 2003–2007, 2008–2012 and 2013–2017. Over 35 years the number of research papers on PD increased 33-fold: 885 papers in 1983–1987 to 29, 972 in 2013–2017. At the same time the number of countries contributing to PD research increased from 37 to 131. The USA was the most prolific country throughout, followed by several European (UK, Germany, Italy and France) and English-speaking (Canada and Australia) countries. By 2003, several Asian countries (China, South Korea, India and Turkey) emerged with rapid increases in publications related to PD. By 2013–2017, China surpassed all but the USA to rank 2nd globally in productivity. Despite an increase from 4 to 22 African countries publishing PD research from 1983 to 2017, most were either unproductive or contributed ≤5 papers in each five-year period. There has also been a 12-fold increase in the number of journals (232–2824) containing papers on PD. In 2013–2017 three PD-focused journals ( Parkinsonism & Related Disorders, Movement Disorders and Journal of Parkinson's Disease ) contained 6.8% of all PD papers while a large majority (82.5%) of journals published ≤ 10 papers. This quantitative study complements the numerous extant qualitative reviews to provide a global perspective on PD research. Highlights: From 1983 to 2017: The scientific literature on Parkinson's disease increased 33-fold. The number of countries publishing Parkinson's disease papers went from 37 to 131. The number of journals publishing Parkinson's disease research increased 12-fold. Currently: The countries contributing the largest percentages of published papers are: USA, China, UK, Germany, Italy, and Canada. Ten journals concentrate nearly 19% of the Parkinson's disease literature.